1981
DOI: 10.1002/chin.198116282
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: CONDENSED AS‐TRIAZINES. VIII. DIRECT SYNTHESIS OF 1‐SUBSTITUTED TRIAZOLES FUSED TO BENZO‐AS‐TRIAZINE AND PYRIDO(2,3‐E)‐AS‐TRIAZINE RINGS

Abstract: Ringschlußreaktionen zur direkten Synthese der beiden Titelringsysteme werden untersucht, wobei beide Systeme vergleichend betrachtet werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The structure-activity correlation study using structural derivatives of CTBT revealed that chlorine on the benzene ring as well as the tetrazolo ring are essential both for antifungal and chemosensitising activities of CTBT. When chlorine was substituted with a hydrogen or methyl group, the chemosensitising activity of corresponding compounds, tetrazolo [5,1-c]benzo [1,2,4]triazine [42] and 7-methyltetrazolo[5,1-c]benzo [1,2,4]triazine [43], was lost and their antifungal activity was diminished. Substitution of nitrogen in the tetrazolo ring with a carbon atom bound to hydrogen (7-chloro [1,2,4]triazolo [3,4-c]benzo [1,2,4]triazine [42]) or to different chemical groups such as C-Br (1-bromo [1,2,4]triazolo [3,4-c]benzo [1,2,4]triazine [41]) or C-CH 3 , C-NH-NH 2 (data not shown) led to loss both of the antimicrobial and chemosensitising activities of corresponding compounds under used experimental conditions (Fig.…”
Section: Screening Of a Small Compound Library For Modulators Of Drugmentioning
confidence: 98%
“…The structure-activity correlation study using structural derivatives of CTBT revealed that chlorine on the benzene ring as well as the tetrazolo ring are essential both for antifungal and chemosensitising activities of CTBT. When chlorine was substituted with a hydrogen or methyl group, the chemosensitising activity of corresponding compounds, tetrazolo [5,1-c]benzo [1,2,4]triazine [42] and 7-methyltetrazolo[5,1-c]benzo [1,2,4]triazine [43], was lost and their antifungal activity was diminished. Substitution of nitrogen in the tetrazolo ring with a carbon atom bound to hydrogen (7-chloro [1,2,4]triazolo [3,4-c]benzo [1,2,4]triazine [42]) or to different chemical groups such as C-Br (1-bromo [1,2,4]triazolo [3,4-c]benzo [1,2,4]triazine [41]) or C-CH 3 , C-NH-NH 2 (data not shown) led to loss both of the antimicrobial and chemosensitising activities of corresponding compounds under used experimental conditions (Fig.…”
Section: Screening Of a Small Compound Library For Modulators Of Drugmentioning
confidence: 98%